PENERAPAN SENAM LANSIA SEBAGAI UPAYA KOMPLEMENTER BIDAN DALAM MENURUNKAN TEKANAN DARAH PADA PEREMPUAN MENOPAUSE DI KOMUNITAS DESA DELI TUA BARAT - Ariani, Peny; Sitepu, Marlen Sadrina; Halawa, Kris Angelina; Hadi, Milvan; Hariati, Erni; Hutabarat, Vitrilina (Jurnal Pengabdian Masyarakat Putri Hijau, 2025)
Hypertension is a common health issue frequently experienced by menopausal women. As women enter menopause, their risk of developing hypertension increases by approximately 41% compared to men, primarily due to the decline in estrogen levels during this period (Indalifiany & Suryani, 2024). In Indonesia, hypertension is recognized as one of the leading causes of death. The management of hypertension in menopausal women can involve both pharmacological and non-pharmacological approaches. Pharmacological treatments typically include the use of antihypertensive medications such as diuretics, beta-blockers, and vasodilators (Chobanian et al., 2014). Meanwhile, non-pharmacological interventions like elderly gymnastics have been shown to effectively help reduce blood pressure. The exercise facilitates the release of heat, lactic acid, and carbon dioxide from the muscles, improving blood circulation and oxygen supply to muscle tissues, which promotes vasodilation, capillary relaxation, and ultimately lowers blood pressure (Muharni & Christya Wardhani, 2020). In a community service activity conducted in West Deli Tua Village, it was found that 80% of 30 participating menopausal women experienced an increase in knowledge about the benefits of elderly gymnastics. Additionally, a noticeable reduction in blood pressure was observed among participants after engaging in the exercise program.